HUKUM TUKAR CINCIN PADA SAAT KHITBAH MENURUT PANDANGAN HUKUM ISLAM - Umami, Hafidhul (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2024)
The engagement process is carried out with various different processions in each region, depending on the customs of the region. Nowadays, the factor of modernization has brought foreign culture into a trend and lifestyle that is followed by the wider community. The proposal which is also commonly called engagement in today's era is carried out with a ring exchange procession which is originally not part of Islamic law. The ring exchange tradition is the procession of attaching rings to the bride and groom during the proposal procession witnessed by each family as a symbol of interest or commitment to move towards something more serious. This ring exchange procession is also considered a complement to the engagement event that is carried out. The ring exchange is generally carried out with each party who is engaged putting the ring on their partner's finger in turn. In this procession, it is not uncommon for men and women to touch each other directly to put on the ring. As for the ring used in the exchange, it is a ring made of gold, while the use of gold rings for men is forbidden or prohibited by Islamic law.